Optimalisasi Kemampuan Penulisan Karya Ilmiah Melalui Pelatihan untuk Meningkatkan Profesionalisme Guru-Guru di SMP Negeri 1 Jayapura: Pelatihan Penulisan Karya Ilmiah - Jonner Nainggolan; Virman Virman (Universitas Majalengka, 2023)
Teachers according to Law No. 14 of 2005 are professional educators, therefore increasing self-competence is a must. One of the self-competencies that must be developed is increasing research and disseminating it in journals. The teacher's current problem is not being able to make publications, some of the things that are considered as the cause include teachers not understanding the signs in making publications, teachers feel burdened by school administration, and others. The purpose of this service activity is to provide training on writing scientific papers, especially in journals. This activity was attended by 20 teachers, the training material included guidelines for making publications and how to submit to journals. The material is delivered in the form of lectures. The results show that the teacher is very happy and feels helped by this activity. In terms of the process, it is included in the good category, this can be seen from the attendance of the participants which reached 100%, all participants seemed very enthusiastic, enthusiastic and motivated to take part in this activity.